Transformation: Troublemaker - Tkacheva, Marina (project baikal, 2019)
The article is devoted to “Transformation”, a new plein-air sculpture by D. Namdakov. It describes the symbolics of the sculpture, its penetration into the contemporary mentality and its location on the territory of Siberian Federal University in Krasnoyarsk. The article points out its originality and continuity of traditions. It speaks about the eclecticity of contemporary artistic perception and the diversity of interpretations of the artistic spirit of the sculpture.